“Repotenciación y automatización de una clasificadora de granos para el Proyecto de Granos Andinos de la Universidad Técnica de Cotopaxi” - Iza Laica, Kevin Alexander (2023)
In the present technological proposal, the automation of a grain classifier is presented to reduce the process time and the amount of impurities in the Andean Grain Project of the Technical University of Cotopaxi, for this the classifying machine that allows the user to select the size of grains of three different types large, medium and small, the experimental tests were carried out for chochos, maize and beans. The proposed methodology is focused on the selection of electronic equipment such as frequency inverter, PLC and HMI screen, which will serve for the construction of the automated system, as well as the corresponding calculations to determine the sizing of the control panel.